Extension worker as a leader to farmers: Influence of extension leadership competencies and organisational commitment on extension workers' performance in Yemen - Khalil, Ali Hassan; Ismail, Maimunah; Suandi, Turiman; Silong, Abu Daud (Journal of International Social Research, 2008)
Agriculture extension primarily deals with human resource development (HRD) and the transfer of technology and knowledge from agricultural research centres to farmers. Improving human resource development (HRD) within rural community is essential for agriculture and community development. Extension workers are professionals in the extension system responsible for developing individuals in the community. Hence, as the profession of extension work continues to expand, it is necessary to identify leadership skills possessed by the agricultural extension workers in order to gauge their performance in the extension system. Therefore, there is a need first to gauge performance of extension workers and a need to determine predictors of performance. This article examined the relationship between leadership competencies and organizational commitment with performance as perceived by the agricultural extension workers and the predictors of performance. The leadership competencies variables and commitment are important attributes of a leader. Data were collected from 290 respondents who were selected based on stratified sampling technique. The stratification was based on highlands, coastal and desert regions. The findings showed that four variables were significantly contributed to the level of extension workers’ performance. The variables are competencies in program implementation, program evaluation and program planning as well as organizational commitment. These predictor variables explain 45.3 % of the variance in the job performance of extension workers. The study suggests that relevant ministry such as the ministry of agriculture should take into account the leadership characteristics of extension workers and how to improve those competencies as well as organizational commitment in order to upgrade their performance in developing rural communities through extension services.